2023
DOI: 10.3390/ma16020673
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Specimen Size Effect on the Fracture Energy of Macro-Synthetic-Fiber-Reinforced Concrete

Abstract: The most frequently used construction material in buildings is concrete exhibiting a brittle behaviour. Adding fibers to concrete can improve its ductility and mechanical properties. To this end, a laboratory study was conducted to present an experimental model for the specimens’ size effect of on macro-synthetic fiber-reinforced concrete using variations in fracture energy. Composite concrete beams with different thicknesses and widths were made and tested under mode I to obtain (1) fracture toughness, (2) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…9 gives the behavior of K 1C , where K 1C increases as the a/d ratio increases, similar to the results found in the literature [3,4]. Furthermore, the value of K 1C increases as the b expands, as found in [17]. The load-deflection curves depicted in Figs.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…9 gives the behavior of K 1C , where K 1C increases as the a/d ratio increases, similar to the results found in the literature [3,4]. Furthermore, the value of K 1C increases as the b expands, as found in [17]. The load-deflection curves depicted in Figs.…”
Section: Resultssupporting
confidence: 86%
“…Researchers have suggested that reflective cracks are primarily a result of a combination of Mode I and Mode II fracture, or Mixed-Mode fracture under the applied stress that the three-point bending beam test is appropriate for evaluating fractures. A study conducted by Daneshfar, M., and Hassani [17] investigated the effect of adding short fibers to concrete. They conducted experiments to analyze the effects of specimen dimensions on synthetic FRC.…”
Section: Introductionmentioning
confidence: 99%